Peran Profitabilitas dalam Memediasi Pengaruh Struktur Kepemilikan Terhadap Nilai Perusahaan pada Perusahaan F&B (2019-2023) - Naiborhu, Gaby Anthonioner; Sianturi, Jeudi A.T.P; Sihite, Mislan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study was to obtain empirical evidence of profitability in mediating ownership structure on firm value. The sample used in this study were all Food and Beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period using purposive sampling method, namely 48 companies. The software analysis used is WarpPLS 8.0. The results of this study indicate that ownership structure and liquidity directly have a positive and significant effect on firm value. While leverage shows that it has no effect on firm value. Ownership structure has a positive and significant positive effect on profitability. The test results prove that profitability is able to partially mediate the effect of ownership structure on firm value.